An updated review of the genus Martensopoda Jäger, 2006 (Araneae: Sparassidae: Heteropodinae) - Sankaran, Pradeep M.; Malamel, Jobi J.; Joseph, Mathew M.; Sebastian, Pothalil A. (Zootaxa, 2015)
A new species of the huntsman spider genus Martensopoda Jäger, 2006, M. sanctor sp. nov., is described and illustrated from the southern Western Ghats of India. Detailed first description and illustration of the male of M. minuscula (Reimoser, 1934) with a redescription and illustration of its female are provided. The female of M. transversa Jäger, 2006 is redescribed and illustrated. An identification key and a distribution map of all three Martensopoda species are presented.